When wells are welfare and not threat to farmers' well-being: Groundwater markets and politics in West Bengal, India - Mukherji, Aditi (2007)
In this paper, I will argue that groundwater irrigation in well-endowed alluvial aquifers of the Ganga-Meghna-Brahmaputra (GMB) is a source of wealth and welfare (and not threat) to its largely poor and agrarian population. I will illustrate this with the case of West Bengal. First, based on secondary data, I will show that groundwater irrigation has been instrumental in agrarian growth in West Bengal. Then, based on primary data collected from 580 respondents in 40 villages in the state, I will specially focus on the beneficial impact of groundwater supported private irrigation services market in distributing benefits of irrigation to those who do not own water extraction mechanisms (WEMs). In doing so, I will capture the spread and extent, as well as functioning and impact of informal groundwater markets. The paper will show that the situation in West Bengal is in sharp contrast to the groundwater situation in many other parts of India such as Gujarat and Tamil Nadu. However, unfortunately, the dominant discourse in the field of groundwater studies in India has been that of depletion and scarcity so much so that the groundwater policies even in a well- endowed state such as West Bengal have been unduly influenced by this dominant discourse. The result has been that of a paradox: little groundwater regulation where resource conditions are precarious (e.g. Gujarat, Tamil Nadu) and strict regulation where little is needed (e.g. West Bengal). This brings us to the arena of politics of policy making, especially how 'scientific' information is processed through the lens of politics and vice- versa. Political ecology of groundwater irrigation will be briefly discussed in the last section of this paper.